the Effect Of Competency and Professional Skepticism On Audit Quality (Empirical Study at Public Accountant Office Bandung): Audit - RAHMAN, ERPI; Royani, Solihin; Tuasalamony, Ardhiatul Halima; Putri, Billa Adzani (Jurnal Ekuisci, 2024)
Abstract. The study aims to determine the effect of competency and professional skepticism on audit quality in Public Accountant Offices (KAP) in Bandung. This study uses a quantitative research method. The sample in this study consists of 35 respondents from 48 questionnaires distributed to auditors working at Public Accountant Offices (KAP) in Bandung. Data analysis in this study uses multiple linear regression models with IBM SPSS (Statistical Program for Social Science) software version 29.0. The results of this study indicate that the competency and professional skepticism variables simultaneously have a positive and significant effect on audit quality. Partially, the competency variable has a positive and significant effect on audit quality, while professional skepticism does not have a significant effect on audit quality. The Adjusted R Square value is 0.553 or 55.3%, while the remaining 44.7% is explained by other variables aside from the independent variables in this study.